2023
DOI: 10.1111/1365-2435.14254
|View full text |Cite
|
Sign up to set email alerts
|

Spore production monitoring reveals contrasting seasonal strategies and a trade‐off between spore size and number in wood‐inhabiting fungi

Abstract: Spore production monitoring reveals contrasting seasonal strategies and a trade-off between spore size and number in woodinhabiting fungi. Functional Ecology, Early View.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…In forest traps, 83% of all beetle species were caught before July (Burner et al, 2022), indicating that the flight period of most forest beetles is indeed early in the season. For fungus‐visiting beetles, this seasonal pattern could also be related to the spore production of F. pinicola , which is largest in spring (Norros et al, 2023; Nuss, 1986). True flies, slugs and centipedes exhibited seasonal variation as well, but appeared later in the season, indicating that they are less dependent of sporulation rates.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In forest traps, 83% of all beetle species were caught before July (Burner et al, 2022), indicating that the flight period of most forest beetles is indeed early in the season. For fungus‐visiting beetles, this seasonal pattern could also be related to the spore production of F. pinicola , which is largest in spring (Norros et al, 2023; Nuss, 1986). True flies, slugs and centipedes exhibited seasonal variation as well, but appeared later in the season, indicating that they are less dependent of sporulation rates.…”
Section: Discussionmentioning
confidence: 99%
“…invertebrates seemed to correlate with the fungal sporulation period, that is, in spring and at night (Norros et al, 2023;Nuss, 1986), these visitors could potentially be dispersing the spores of F. pinicola. In the same study area, Lunde et al (2023) found that all beetles visiting 3), which are detailed in Materials and Methods.…”
Section: Chilopodamentioning
confidence: 99%
See 3 more Smart Citations